NMR Studies on How the Binding Complex of Polyisoprenol Recognition Sequence Peptides and Polyisoprenols Can Modulate Membrane Structure - Zhou, Guo-Ping; Troy II, Frederic A. (Current Protein and Peptide Science, 2005)
The glycosyl carrier lipids, dolichylphosphate (C95-P) and undecapreylphosphate (C55-P) are key molecular players in the synthesis and translocation of complex glycoconjugates across cell membranes. The molecular mechanism of how these processes occur remains a mystery. Failure to completely catalyze C95-P-mediated N-linked protein glycosylation is lethal, as are defects in the C55-P-mediated synthesis of bacterial cell surface polymers. Our recent NMR studies have sought to understand the role these
Keywords: polyisoprenol (dolichol) structure